GERAKAN PRODUKTIF DAN POLA HIDUP SEHAT DI TENGAH PANDEMI COVID-19 DESA PANUTAN - Leni Anggraeni; Muhamad Muslihudin; Rudi Aprianto (Jurnal PkM Pemberdayaan Masyarakat, 2022)
Coronavirus or Covid-19 is a contagious infectious disease caused by the novel coronavirus or a new type of coronavirus. Covid-19 stands for Corona (CO), Virus (VI), Disease (D, disease) which was discovered in 2019. This is greatly influenced by the clean and healthy lifestyle of the community. For people who are still indifferent to the coronavirus, therefore the movement for a healthy lifestyle in the midst of the covid-19 pandemic needs to be carried out a lifestyle that pays attention to all aspects of health conditions, starting from food and drinks, nutrition consumed, and our daily behavior, both it's in an exercise routine that will certainly maintain health conditions and will also avoid all things that can cause disease for our bodies, especially health is what we all desire. Thus, socialization of productive movements and healthy lifestyles such as implementing 5M as a solution is carried out. With this socialization, the public is aware of the importance of health during the pandemic so as not to transmit the danger of the coronavirus